94.2k views
0 votes
What is the value of x in the solution

y=x-1
y=2x+1

User Nofoobar
by
4.9k points

2 Answers

6 votes

First, we replace y with the first equation, so it would look like this:



x - 1 = 2x + 1


Then we start simplifying:



x-2x = 1+1


At last we do:



-x = 2 or
x = -2


So the answer is: -x = 2 or x = -2


Hope this helped! c:

User Longwalker
by
5.6k points
4 votes

Assuming that these equations depend on each other, We can use substitution to figure out what x is equal to. Since both equations have a certain value of x equal to y, we can substitute one of the equations into the other.


y = x - 1


Use substitution


x - 1 = 2x + 1

x = 2x + 2

-x = 2

x = -2

User Whichdan
by
5.7k points